HAEMOLYTIC ANAEMIA AS A COMPLICATION OF INTRAVENOUS IMMUNOGLOBULIN THERAPY. Issue 12 (15th November 2016) - Salam, Sharfaraz; Woodall, Amanda; Gosal, David
Abstract : Aim: To monitor a series of thirty consecutive patients receiving their first dose of intravenous immunoglobulin for haemolytic anaemia. Methods: Prospectively, thirty consecutive patients with Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) receiving their first high dose of immunoglobulin therapy were monitored for clinical and laboratory features of haemolytic anaemia. Results: Three patients were identified with features suggestive for haemolysis. Conclusion: We confirm the literature findings of a strong association between high dose intravenous immunoglobulin therapy and haemolysis in neurology patients receiving immunoglobulin therapy.